2022
DOI: 10.33086/snpm.v1i1.862
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Higiene Dan Sanitasi Santri Di Pondok Pesantren Salafiyah Nurul Ulum Gresik Bersama Industri Pt. Terminal Petikemas Surabaya

Abstract: Penerapan hygiene dan sanitasi di Pondok pesantren sangat didukung oleh pemahaman santri dan pengelola pondok. Namun semua itu juga didukung oleh kemmapuan pondok dalam melengkapi saran dan prasarana praktek hygiene dan sanitasi di pondok pesantren. Kegiatan ini bertujuan untuk memberikan peningkatan pemahaman kepada santri dan pengelola terhadap penerapan hygiene sanitasi di pondok pesantren. Kegiatan dilaksanakan secara langsung (luar jaringan). Diataranya melalui kegiatan sosialisasi, praktik cuci tangan, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The control of emitted dust particles is being more significant [2,3]. Authors have shown that, construction industries are the major sources of dust pollution and construction practitioners may face long-time illness or premature death [4,5]. The worldwide Environment policies are being improved and becoming stricter for industries.…”
Section: Introductionmentioning
confidence: 99%
“…The control of emitted dust particles is being more significant [2,3]. Authors have shown that, construction industries are the major sources of dust pollution and construction practitioners may face long-time illness or premature death [4,5]. The worldwide Environment policies are being improved and becoming stricter for industries.…”
Section: Introductionmentioning
confidence: 99%